2011
DOI: 10.1007/s11771-011-0712-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of fence effects on dust emission into atmosphere from open storage piles

Abstract: The results obtained from the research on the behaviour of fences (solid and porous) in the protection against particulated material emission to the atmosphere from open storage piles, are presented. This research was carried out through computational fluid dynamics (CFD) simulation by software Ansys CFX-10.0 in 3D, with K-epsilon being considered in the turbulence model. The efficiency of the use of porous fences as a protection against the wind flow, which interacts with an open storage pile, is shown. The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Mining companies play an important role in the country's export potential, as well as in the sustainable development of the regions where they are located [1][2][3][4][5]. However, each such enterprise is accompanied by waste storage facilities for mineral processing waste, which are mostly artificial formations on the earth's surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mining companies play an important role in the country's export potential, as well as in the sustainable development of the regions where they are located [1][2][3][4][5]. However, each such enterprise is accompanied by waste storage facilities for mineral processing waste, which are mostly artificial formations on the earth's surface.…”
Section: Introductionmentioning
confidence: 99%
“…Taking into account the complex geometry of the outer surface of the MPW embankment dam, formed by the sequential repetition of the slope and the dam shelf when moving to a new embankment tier (figure 1), powerful aerodynamic models -CFD modelsshould be used to theoretically solve the problem of determining the wind speed along the beach. This approach has been successfully used by domestic and foreign experts in modeling the wind regime [1,2]. However, well-known models of this class, such as ANSYS CFX, require a very significant amount of time to calculate the airflow velocity field when flowing around structures with such a complex geometric shape as the MPW.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, particulate pollution has become a significant part of air pollution and occupied about 40%-80% of the total emission particulate matter. [1][2][3] In order to control the dust emissions and reduce the material loss, scholars and enterprises have begun to pay attention to the membrane structure used as storage for coal or other mineral aggregate, 4 such as a membrane structure coal storage was used by Shenhua Bayan Nur Energy Ltd. 5 Li and Li 6 analyzed the advantages of the closed fabric membrane structure coal storage, and concluded that the initial investment of the fabric membrane structure using polyvinyl chloride (PVC) saved 50%, the membrane structure has good self-cleaning performance and short construction period compared with the conventional spherical grid structure. Hu et al 7 designed a building integrated photovoltaic-thermal (BIPV/T) collector ethylene tetrafluoroethylene (ETFE) cushion structure system, the structure feasibility was validated by system temperature and pressure performance, the study reveals that the technical feasibility of ETFE cushion membrane structure integrated photovoltaic.…”
Section: Introductionmentioning
confidence: 99%